2018
DOI: 10.3390/ijerph15102071
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Versus Nontargeted Communication About Electronic Nicotine Delivery Systems in Three Smoker Groups

Abstract: Background: This study used an audience segmentation and message targeting approach to identify three distinct smoker groups—Older Freedom Smokers (OFS), Reluctant Smokers (RS), and Young Enthusiasts (YE)—and examined whether an electronic nicotine delivery systems (ENDS) message targeting each smoker group (targeted message) was associated with more health-enhancing outcomes than messages targeting other groups (nontargeted messages). Methods: An online experiment was conducted among 580 adult smokers with 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…After removal of duplicates and publications that did not meet the inclusion criteria, a total of 31 articles were included [7,8,24–28,34–57] (Table 3) reporting results from studies involving a total of 52 425 participants (ranging from 95–16 051). Twenty‐six of the included studies were experiments and the remaining were cross‐sectional surveys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of duplicates and publications that did not meet the inclusion criteria, a total of 31 articles were included [7,8,24–28,34–57] (Table 3) reporting results from studies involving a total of 52 425 participants (ranging from 95–16 051). Twenty‐six of the included studies were experiments and the remaining were cross‐sectional surveys.…”
Section: Resultsmentioning
confidence: 99%
“…A study exploring the impact of a public education campaign about relative safety of NVPs reported that the intervention was associated with an increase in smoker motivation to quit [49]. Two studies found no association between message exposure (a targeted message stratified by smoker group [52] and a nicotine education message [37]) and smoker intention to quit smoking. Exposure to relative risk messages (compared to control conditions such as a bottled water advert) was associated with higher intentions among smokers to switch from smoking to vaping [35,54].…”
Section: Resultsmentioning
confidence: 99%